The Influence of Gamification on Repurchase Intention at E-Marketplace from a Habit Perspective - Bekti Suratmanto; Yonathan Dri Handarkho; Andi Wahju Raharjo Emanuel (Journal of Information and Organizational Sciences)
This study investigates how gamification influences habit formation and repurchase intention in Indonesian e-marketplaces, focusing on key elements such as points, rewards, badges, and challenges. Using the Stimulus-Organism-Response (SOR) model and habit formation theory, the research examines how user engagement drives repeat purchasing behavior. Data were collected from 375 Shopee and Tokopedia users via an online survey, and the hypotheses were tested using Structural Equation Modeling (SEM). The results reveal that gamification significantly enhances customer engagement, which in turn strengthens habitual use and positively impacts repurchase intention. Among the gamification elements, rewards emerged as the most influential driver of repeat purchases, suggesting that incentive-based mechanisms are particularly effective in promoting customer retention. Unlike previous studies that primarily emphasize engagement and loyalty, this research highlights the specific role of gamification in shaping behavioral habits that lead to sustained purchasing. By integrating habit theory into the SOR framework, the study offers a fresh perspective on long-term consumer behavior in digital commerce. These findings have practical implications for e-marketplace platforms seeking to optimize their gamification strategies to maintain engagement and boost sales. Overall, the study emphasizes the importance of habit formation as a key factor in enhancing customer retention through gamification.